Mechanisms to Increase Competitiveness in the Service Sector - Kholboyevich, Kholboyev Umid (European Journal of Life Safety and Stability (2660-9630), 2022)
Competitiveness is an important market mechanism for enterprises to adapt to market conditions and express themselves.